Exploring the Mediating Role of Psychological Resilience in Enhancing Employee Empowerment and Organizational Commitment: A Dual-Theory Approach PsyCap and JD-R Perspective - Adawiah, Andi; Putra, Aditya Halim Perdana Kusuma (International Review of Management and Marketing, 2025)
This study aims to investigate the relationship between Employee Empowerment Strategy (EES), Cognitive Balance (CB), Emotional Intelligence (EI) as independent variables, Psychological Resilience (PR) as an intervening variable, and Job Satisfaction (JS), Team Productivity (PT), Employee Loyalty (EL), and Organizational Commitment (OC) as dependent variables. To achieve good representation and accurate results, a sample of 250 private sector employees was selected using stratified random sampling technique. This technique was chosen so that the sample includes variations in terms of organizational level, industry sector, and demographic background, so that the research results can reflect the diversity that exists in the wider population. Participation eligibility criteria included: (1) being employed in a private sector organization for a minimum of 12 months, (2) being at least 25 years old, and (3) voluntarily consenting to participate in the study. This study then uses a quantitative analysis approach with SEM-PLS as a data analysis and hypothesis testing tool. The results of this study state that, either through a direct relationship between the independent variable and the dependent variable or through an intervening variable (indirect effect), all test relationships state a positive and significant effect. Theoretically and managerially, this study also contributes theoretical and practical knowledge, especially in the development of the Psychological Capital Theory and the Job Demands-Resources (JD-R) theory.